ANALISIS DERET FIBONACCI DAN GOLDEN RATIO PADA SIMBOL HATI BERDASARKAN PROPORSI LOGO DESAIN PRODUK APPLE - Puputi Wulandari; Hartanto Sunardi (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2015)
Commonly Fibonacci sequence is understood as sequence which is gotten from relation orderly start from 0 and 1, then next number is gotten from the addition of two number before it. If number in Fibonacci sequence are divided with previous number will be gotten number which the value will be same after the comparison approaching 1,618… these number are known as Golden Ratio or symbolized as (phi).This study aims to analyze mathematically Heart symbol and arrange the element in terms of the Fibonacci sequence and Golden Ratio based on logo proportion product design Apple . Then the ratio of the beauty of the Heart figure before and after arrangements were analyzed using the Wilcoxon test with 18 respondents of the students audience Junior High School 2 Taman Sidoarjo. In addition, based on the value of statistical tests, proven heart fibo curve more beautiful than heart curve. Keywords : Fibonacci, Golden Ratio, Heart Curve, Apple Design, Wilcoxon